2015
DOI: 10.1097/bpb.0000000000000144
|View full text |Cite
|
Sign up to set email alerts
|

Tibial shaft fractures in adolescents

Abstract: This study retrospectively analyzed cast treatment of 75 adolescent closed tibial diaphyseal fractures. The average age was 13.3 years (range, 10-17.4 years). Of the patients, 21% (16/75) required cast change/wedging in the clinic for loss of reduction, and three patients (4%, 3/75) injured in vehicular collisions had failure of cast treatment, requiring an unplanned surgical intervention. Initial and immediate postreduction radiographic deformities were greater (P<0.05) in patients who required cast change/we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Patients treated with instable fractures of both, tibia and fibula were mainly treated with ECMES ( Figure 2D) and may require additional stability till consolidation provided by cast. Which is in accordance with literature showing that immobilization in a cast for longer than 3 months was required in nearly 60% of patients with a combined fracture of tibia and fibula (23). The advantage of ECMES is the insertion at a position distinct from traumatic wounds, and the minimal additional damage to surrounding tissue, which is particularly important in the context of high-energy trauma settings.…”
Section: Discussionsupporting
confidence: 89%
“…Patients treated with instable fractures of both, tibia and fibula were mainly treated with ECMES ( Figure 2D) and may require additional stability till consolidation provided by cast. Which is in accordance with literature showing that immobilization in a cast for longer than 3 months was required in nearly 60% of patients with a combined fracture of tibia and fibula (23). The advantage of ECMES is the insertion at a position distinct from traumatic wounds, and the minimal additional damage to surrounding tissue, which is particularly important in the context of high-energy trauma settings.…”
Section: Discussionsupporting
confidence: 89%
“…Treatment failure with conversion to open reduction occurred in 2/74 (2.7%) individuals who underwent casting without manipulation and 6/36 (16.7%) treated with CRC. In this series, treatment failure of casting was associated with greater initial fracture displacement and severity, consistent with prior studies of midshaft tibia fractures in adolescents [15,17].…”
Section: Discussionsupporting
confidence: 89%
“…Ho et al . [17] reported that 16/75 adolescents with midshaft tibial fractures treated with casting required a cast change or cast wedging. Three individuals were ultimately converted to operative treatment, supporting casting as an effective treatment for tibial shaft fractures in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of surgical interventions increased significantly with the increase in the age of the patient cohort. Ho et al reported in a retrospective study that 4% (n=3) of the adolescent patients out of 75 ultimately needed surgical fixation of tibial fractures due to changed position following long leg cast management [ 23 ]. The proportion of patients requiring surgery after a period of casting in our series is similar.…”
Section: Discussionmentioning
confidence: 99%